Russia and the West: Contradictory Dialogue - T. V. Zonova; A. Giannotti (Vestnik MGIMO-Universiteta, 2020)
The authors focus on the historical evolution of the relations between Russia and the West and attempt to suggest their own vision on the future prospects. The aforementioned relationship span centuries of history. At times, these relations were peaceful, while at times, “Russophobia,” on the one hand, and anti-Western feelings, on the other, served as a backdrop to military clashes. The authors pay special attention to the events of recent decades that have posed new threats and challenges. Given the current militarization and securitization of world politics, strategic stability, which is highly dependent on relations between Russia and the West, is being called into question. After Crimea became part of the Russian Federation and hostilities began in the Donbass region, anti-Russian sanctions were imposed, and Russia, in turn, passed counter-sanctions legislation. Therefore, Russia’s relations with the United States have sharply deteriorated. Likewise, comprehensive ties with the European Union have been frozen. The West, mainly the United States and UK, has launched anti-Russian campaign. As a mirror response Russian media also dazzles with speculations about "the decay and decline of the West". Consequently, Russia has declared its “shift to the East”. A real psychological war is being waged between Russia and the West, with both sides resorting to the latest advanced technology in their propaganda. A number of Russian politicians grew supportive of some Western movements and parties of the right spectrum, the so called “sovranists” who aimed at withdrawing their countries from international treaties and unions. Meanwhile, Donald Trump’s victory in the 2016 elections as the Republican right-wing candidate, who pledged to improve US-Russia relations, was much praised in Moscow. The authors conclude that recent constructive Russian-American meetings and the 2019 meeting in the Normandy Format which contributes to conflict resolution in the South-East of Ukraine can facilitate positive developments of Russia’s relations with the West.